The Impact of IFRS Adoption on Financial Performance: Evidence from European Firms - The Impact of IFRS Adoption on Financial Performance: Evidence from European Firms (International Journal of Innovative and Applied Finance, 2019)
login and register and pay the fees to get an open access to content